An efficient motion planning framework for four-wheel steering autonomous vehicles using Lazy Edge-Based A* and adaptive RK4-MPC - Deyndrawan Sutrisno; Subiyanto Subiyanto; Arimaz Hangga; Aldias Bahatmaka; Nur Azis Salim; Elfandy Yunus; Muhammad Hilmi Farras; Setya Budi Arif Prabowo (National Research and Innovation Agency, 2026)
This work presents an efficient motion planning framework for four-wheel steering (4WS) autonomous vehicles operating in complex and unknown environments. To improve planning efficiency, the framework employs a lazy edge-based A* (LEA*) algorithm for global path planning, adaptive fourth-order Runge–Kutta model predictive control (RK4-MPC) for trajectory tracking and motion execution, and wheel force distribution control (WFDC) to ensure stable motion during steering maneuvers. Quantitative results show that the LEA* reduces planning time by 87.5 % edge evaluations by 96.1 % compared to conventional A*, while improving path smoothness by 51 %. The integration of adaptive RK4-MPC with WFDC achieves the lowest tracking error and heading error of 34.8 % and 37.5 % compared to OMNI, and 28.6 % compared to S-4WS. In addition, the proposed method reduces the wheel slip ratio 88.4 % better than OMNI and 46.7 % better than S-4WS, while also reducing yaw acceleration by 50 % compared to both baselines. For computational efficiency, the proposed framework achieves a search time of 0.5234 s, 83.1 % faster than OMNI, and 37.1 % faster than S-4WS, and an optimization time of 1.4892 s, 30.3 % faster than S-4WS. Overall, the proposed framework improves motion planning efficiency while maintaining smooth and stable motion in simulation.